Living-dwelling | the importance of half-private spaces in the neighborhoods on the city borderline - Zinoski, Mihajlo (Emerald Publishing Limited, 2020)
Purpose – The purpose of this paper is to present the participatory action project, in an attempt to redefine the aprioristic approach, which does not bring significant results for the local community regarding the sustainable concept as an estimative goal. The purpose of introducing the process management (PM) as a technique was to incorporate the collaboration between academic research with ongoing activities of local authorities, and furthermore to preserve living and dwelling patterns to make them sustain within the neighborhood in time. Design/methodology/approach – PM is a method of approaching planning that can be used in complex, unpredictable situations common in the field of development and social change. The method allows stakeholders to pursue different goals or activities within a common project. Under such circumstances, the planning process must respond to many interests as a key aspect of the public interest of a particular community. This concept helps planners by anticipating the precise events and activities to satisfy the larger goals and processes. Findings – This study sets out with the aim to establish sustainability definition in this case study, i.e. based on the notion of the ability of future generations to meet their own needs, the management of the project described in these participatory activities has attempted to resolve the complexity of stakeholder positions in the contemporary community. Emphasizing the social content, general and specific objectives of the project interact and evolve during this process of implementation of sustainable methodology and become the subject to negotiations and compromises, which change during the process. Research limitations/implications – The survey could help to get the needed information to create correlated activity diagrams. They represent the actual and the proposed situation in the neighborhood regarding social interaction between the dwellers and their interlock of interests on different scales. These are highly mutable components that depend on a certain period. The hypothesis regarding certain research problem could give significant statistical differences, but depend on relevant survey questions. Practical implications – A common topic is established – the importance of half-private spaces. The students have learned how to create and use analytical tools in the process of creating a program that has social significance for the inhabitants. In terms of the study curriculum, the students benefit from this project as a part of their education process. Local authorities and dwellers also become aware of the significance of particular social values regarding property value and land use assessment. Social implications – Social sustainability becomes a project where the planning process must respond to many interests as a key aspect of public interest where municipal sustainability requires self-assessment, to reinforce the connection between citizens and local authorities as their real representatives. Originality/value – The hypothesis regarding social behavior gave significant differences when the following aspects were statistically analyzed: time-sharing between household members, the importance of house yard preferences, barrier properties between households and negotiation boundary between neighbors The author would like to express his deepest gratitude to the students of the Faculty of Architecture- Skopje, especially his assistants Stefani Solarska and Igor Medarski. He would further give his appreciation and gratitude to the local authorities of Ilinden Municipality and the local dwellers for their active participation in the survey.
Keywords: Sustainability, Participatory, Process management, Neighborhood, Social interaction, Self-assessment